A Profile Of Skin Medicine Prescription To General Patients At Kimia Farma Kartini Pematangsiantar Pharmacy - Hutahaean, Andi Josep; Heny Kurniasari; Kezia Tabita Pangaribuan (International Journal of Health Engineering and Technology, 2023)
Skin disease is a disorder that is limited or dominant on the surface of the skin and can be treated in various ways, including topical or oral routes. Some conditions are caused by bacteria, viruses, fungi, parasites or allergic reactions. This study aims to determine the profile of skin drug prescribing at Kimia Farma Kratini Pematangsiantar Pharmacy in June 2022 based on patient characteristics, route of administration, dosage form and variations of the mixture, using retrospective data and descriptive data presentation. The results of this study indicate that from 97 samples of prescriptions in June 2022, most of them were in adult patients 49.48% with the most route of drug administration being topical 53.51%, the most dosage form being cream 53.51%, and variations of the mixture. 47.95% while for non-concoction it is 52.05% based on the total frequency of the number of drugs (342).